AI-Powered Electrocardiography: Can I Get AI Analysis of My ECG? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into clinical practice is rapidly transforming diagnostics, and few areas are as ripe for this revolution as el...
Keywords: Diagnostics; Artificial Intelligence; Patient Care; Precision Medicine; Machine Learning